A family Christmas - Kennedy, Caroline, 1957- (New York : Hyperion, 2007)
Presents a collection of favorite holiday stories and excerpts including "The night before Christmas," by Clement C. Moore; "Little Tree," by e.e. cummings; and "A Christmas carol," by Charles Dickens.
Includes bibliographical references.
Keywords: Christmas -- Literary collections